A prospective, randomized, double‐blinded, placebo‐controlled clinical study on postoperative antibiotherapy in 150 arthroscopy‐assisted tibial plateau leveling osteotomies in dogs. Issue 8 (28th September 2018) - Spencer, Dustine D.; Daye, R. Mark
Abstract: Objective: To determine the influence of a 7‐day course of postoperative antibiotherapy (cefpodoxime) on surgical site infections (SSI) after tibial plateau leveling osteotomy (TPLO). Study design: Prospective, randomized, double‐blinded, placebo‐controlled clinical study. Sample population: One hundred fifty client‐owned dogs, with consent. Methods: Dogs undergoing arthroscopy‐assisted TPLO were randomly assigned to 1 of 2 groups, the placebo group receiving perioperative cefazolin and 7 days of placebo medication after surgery or the treatment group receiving perioperative cefazolin and 7 days of postoperative cefpodoxime. Twenty‐seven factors were analyzed for association with SSI by using univariate analysis, Fisher's exact test, or Wilcoxon rank‐sum test. Results: SSI rates did not differ ( P  = .34) between the placebo group (17%; 95% confidence level [CL] 7.94%‐26.43%) and the treatment group (11% SSI; 95% CL 3.98%‐18.88%). The probability that > 23% of dogs would benefit from postoperative antibiotherapy was less than 5%. The only association between the factors tested in this study and SSI involved the body weight (kg), with each 1 unit increase in kilogram weight increasing the odds of developing an SSI by 4.7%. Conclusion: Although the wide CL may be consistent with a type II error, a 7‐day course of cefpodoxime after arthroscopy‐assisted TPLO did not influence postoperative SSI in the population tested here. In addition, only a small proportion of dogs would benefit from postoperative antibiotherapy under the conditions of our study. Clinical significance: These results should prompt surgeons to reconsider systematic antibiotherapy after TPLO and justify additional studies to determine whether dogs predisposed to infection could benefit from such an approach.